Analysis of the morphological attributes of a sweetpotato collection - Manifesto, Maria Marcela (2010)
The knowledge about the distribution of descriptors of a collection constitutes a useful tool for the management of genetic resources. The object of this work was to evaluate the composition and morphological characterisation of the ‘in vitro’ collection kept at the Gene Bank of the Biological Resources Institute (IRB), INTA Castelar, Argentina, to establish conservation criteria and make available useful data for breeding programmes. This collection, comprising 310 sweetpotato clones, includes landraces, worldwide clones, commercial varieties and breeding material. The descriptors, which presented the highest correlation values, were leaf lobe types, the shape of central leaf lobes and general leaf outline. Cluster analyses showed eight major groups with an average similarity of 0.42 (SE ± 0.005). About 76% of the clones presented unique morphology, whereas 34% of them were distributed in 22 groups that could not be distinguished with this technique. Worldwide germplasm formed a separate group with values of diversity higher than those of the Argentinean clones and no duplicates. A projection of the phenotypic variation among cultivars was obtained through Principal Coordinate Analysis (PCoorA), which confirmed the results obtained by UPGMA analysis, predominant skin colour, secondary skin colour, number of leaf lobes, general leaf outline, petiole pigmentation and predominant colour of vine were the variables that made the highest contribution. Collection composition in reference to flesh and skin colour was also analysed.